2018
DOI: 10.5468/ogs.2018.61.5.636
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactic shock to vaginal misoprostol: a rare adverse reaction to a frequently used drug

Abstract: Misoprostol is widely used in daily practice for induction of labor and cervical dilatation prior to intrauterine procedures, including dilatation and curettage or hysteroscopy. Anaphylactic shock to intravaginal misoprostol can occur not only in pregnant women, as reported in 2 previous cases, but also in a non-pregnant, perimenopausal woman, as in the case described herein. A 49-year-old woman received vaginal misoprostol for cervical ripening prior to hysteroscopic myomectomy and experienced anaphylactic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A case of anaphylactic shock and mycotic necrosis after treatment with artotec, a combination of diclofenac sodium with misoprostol has been reported whereas severe hypotension and anaphylactic shock was reported after receiving vaginal misoprostol for cervical ripening prior to hysteroscopic myomectomy. 7,8 On the contrary, various studies have reported protective effect of misoprostol in allergic diseases. Babakhin et al has shown that misoprostol can inhibit basophil histamine release indicating a potentially beneficial role of PGE1 analogues as pharmacotherapy for allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A case of anaphylactic shock and mycotic necrosis after treatment with artotec, a combination of diclofenac sodium with misoprostol has been reported whereas severe hypotension and anaphylactic shock was reported after receiving vaginal misoprostol for cervical ripening prior to hysteroscopic myomectomy. 7,8 On the contrary, various studies have reported protective effect of misoprostol in allergic diseases. Babakhin et al has shown that misoprostol can inhibit basophil histamine release indicating a potentially beneficial role of PGE1 analogues as pharmacotherapy for allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] This rare adverse effect is not limited to pregnant women and a case of anaphylactic shock has also been reported following vaginal misoprostol administered for cervical ripening to a non-pregnant women posted for hysteroscopic myomectomy. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, prostaglandins may not be used in pregnant women due to complications such as nausea and vomiting, fever and chills, blurred vision, diarrhea, and a bitter taste in the mouth [ 13 , 14 ]. Non-pharmacological methods for cervical ripening and labor induction include espand (steppenraute), dates, flaxweed, and chamomile.…”
Section: Introductionmentioning
confidence: 99%